2012
DOI: 10.1590/s0100-83582012000400022
|View full text |Cite
|
Sign up to set email alerts
|

Variations in weed population densities, rate of change and community diversity in RR-soybeans and RR-maize strip crops under two herbicide strategies

Abstract: Concerns about the sustainability of large-scale, direct-drilled RR-soybeans (Glycine max), and RR-maize (Zea mays) under monoculture in central Argentina are growing steadily. An experiment was conducted during three consecutive years to determine the effects of crops and systems (monocultures and strips) and herbicide strategy on weed density, population rate of change (l), b community diversity (H´), crop yields and Land Equivalent Ratio (LER). Not only crops but also crop systems differentially influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Our data on plant species diversity and community composition of a fallow field support these findings. However, some studies have suggested that herbicides may not reduce the diversity of plant communities in agricultural landscapes 42,43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data on plant species diversity and community composition of a fallow field support these findings. However, some studies have suggested that herbicides may not reduce the diversity of plant communities in agricultural landscapes 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…2) because of different chemical properties, weeding mechanisms, and weed control targets 31,45 . Herbicide types were one of the important factors affecting the diversity of weed communities 42,46 . Furthermore, the response of plant communities to herbicides is related to community characteristics 47,48 .…”
Section: Discussionmentioning
confidence: 99%